DILEMMA OF ACTUALIZATION: A PANOPTICAL VIEW OF FEMININE CONSCIOUSNESS IN BHARATI MUKHERJEE’S SELECT NOVELS (International Journal of Food and Nutritional Sciences, 2022)
Bharati Mukherjee’s creative world is inhabited by the people of various religious faiths, diverse ethnicities and different cultural ethos. An instinctive urge to grapple with cultural dimensions, remarkably defines her best creative impulse. Feminine impulse in Mukherjee’s heroines gave a new wave length to her novels. Her novels can be categorized under the title of post-colonial as well as feminine discourse. Mukherjee’s characterization of hybrid colonial personas re assures their space within their limitations. The fragments of feminine facets bring a new identification for her heroines. The present paper aims to picturize how Mukherjee’s protagonist undergoes a vast span of changes in her search and fight for her emancipation in the novels Jasmine and Desirable Daughters,